Quantitative Performance Analysis of Respiratory Facemasks Using Atmospheric and Laboratory Generated Aerosols Following with Gamma Sterilization - Amit Kumar; D. N. Sangeetha; Ramani Yuvaraj; M. Menaka; Venkatesan Subramanian; Balasubramanian Venkatraman (Aerosol and Air Quality Research)
Abstract The emergence of the recent COVID-19 pandemic has rendered mandatory wearing of respiratory masks by infected persons, frontline workers, security personnel and members of the public. This has caused a sudden shift of focus, and significant demand on availability, effectiveness, reuse after sterilisation and development of facemask. Toward this, three types of masks viz. N95, non-woven fabric and double layer cotton cloth are being used by the majority of the population across the world as an essential inhalation protective measure for suppressing the entry of virus-laden respiratory droplets. The Filtering Efficiency (FE) of these masks are tested for atmospheric and laboratory-generated aerosols of size 1.0 µm and 102.7 nm particles before and after sterilisation and the two flow rate conditions corresponding to normal breath rate and during sneezing/coughing. Sterilisation is carried out using a gamma irradiator containing Co-60 source for the two-dose exposures viz. 15 kGy and 25 kGy. The FE of surgical and cloth masks is found to be in the range of 15.76 ± 0.22 to 22.48 ± 3.92%, 49.20 ± 8.44 to 60 ± 7.59% and 73.15 ± 3.73 to 90.36 ± 4.69% for aerosol sizes 0.3–5.0, 1.0–5.0 and 3.0–5.0 µm atmospheric aerosols respectively. The FE of cloth and surgical masks ranges from 45.07 ± 6.69% to 63.89 ± 4.44% and 56.58 ± 1.69% to 83.95 ± 1.04% for 1.0 µm laboratory-generated aerosol for two flow rate, control and irradiated conditions. The FE of N95 mask is found to be more than 95% for atmospheric aerosol, and 1.0 µm laboratory-generated aerosol. However, FE reduced to about 70% for most penetrating particle size after sterilisation. Further, FE reduced to 84% for the particle > 0.3 µm and to 87% for the particle < 0.3 µm after sterilisation. The reduction in FE for N95 mask after sterilization is associated with the reduction of electrostatic interaction of filter medium with particles laden in the air stream. Instead of disposing of N95 masks after a single use, they can be reused a few times as N70 mask during this pandemic crisis after sterilisation. The use of cotton cloth masks in the general public serves fit for the purpose than surgical masks.